0891 Nightmares Predict Cross-Sectional Risk For Suicidal Ideation, But Not Perceived Stigma In A High-Risk Sample Of U.S. Military Veterans. (12th April 2019) - Hilberg, Amanda M; Murphy, Lauren; Pham, Savannah; Bernert, Rebecca A
Abstract: Introduction: Military suicide is a major public health problem, with veterans comprising 22.2% of all suicide deaths in the United States. Sleep disturbance, widely prevalent in veterans, is a well-established risk factor for suicide. Stigma is well documented as a barrier to treatment, with greater psychopathology linked to higher perceived stigma. Nightmares have utility as a novel treatment target, but have yet to be researched in association with suicidal behaviors and perceived stigma toward treatment. Methods: Participants were screened for high suicide risk and insomnia for inclusion in a suicide prevention trial. Baseline measures included the Quick Inventory of Depressive Symptomatology (QIDS-SR), Suicidal Ideation Intensity Scale (SIS), Beck Scale for Suicide (BSS), Disturbing Dream and Nightmare Severity Index (DDNSI), and Perceived Stigma Scale (PSS). DDNSI scores were hypothesized to predict greater suicidal ideation, independent of depression. Exploratory analyses examined PSS relationships to suicide risk and nightmares. Results: Eighty-one percent of participants (N=77 veterans, 12.9% female) reported lifetime SI ( M age = 44.8; SD =14.1). Clinically significant nightmares were common (>55.8%), consistent with a nightmare disorder ( M =11.9, SD =9.1). On average, perceived stigma fell in the moderate range ( M =14.12, SD =6.46). Bivariate correlations revealed positive correlations between DDNSI, BSS (r=.36, p=.001) and SIS scores (r=.31, p=.01). Multiple linear regression analyses showed that nightmares remained significantly associated with suicidal symptoms (ß=.25, t=2.3, p=.025), independent of QIDS-SR scores. Finally, results revealed significant associations between PSS and suicidal symptoms, but not DDNSI (r=.19, p>.05). Conclusion: Results revealed significant cross-sectional associations between nightmares and elevated suicidal symptoms, independent of depression. Perceived stigma toward psychological problems was predictive of greater suicidal ideation, but not nightmare symptoms, suggesting utility as a non-stigmatizing treatment target. Results highlight the potential importance of nightmares as a highly prevalent and modifiable therapeutic target within military suicide prevention. Support (If Any): This work was supported in part by NIH (K23MH093490; Bernert) and DOD/MOMRP/MSRC funding (W81XWH-10-2-0178; Bernert), an effort supported by the Office of the Assistant Secretary of Defense for Health Affairs.